Kesenjangan Epistemologis Pada Madrasah Ibtidaiyah Kurikulum Fikih: Analisis Terhadap KMA 183/2019 Melalui Kacamata Tradisi Keilmuan Pesantren - Hakim, Faisol; Suharto, Babun; Safe'i, Imam (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2026)
Curriculum studies on Islamic Religious Education (PAI) at the Madrasah Ibtidaiyah (MI) level have focused predominantly on pedagogical methods and content sequencing. The epistemological foundations of the curriculum have received comparatively little critical attention. This study examines the epistemological alignment between KMA 183/2019 the Fikih curriculum for MI and the scholarly knowledge tradition of the Indonesian pesantren, with the aim of identifying structural gaps and their practical implications for Fikih learning at the primary level. A mixed qualitative design combining document analysis and systematic literature review (SLR) was employed. Framework analysis was applied to all 96 Fikih competency standards (KD) across grades I–VI, coded against three epistemological criteria derived from the pesantren scholarly tradition: sanad-based transmission authority, maṣlaḥah orientation, and moral-cognitive integration (adab). The SLR reviewed 38 peer-reviewed sources on pesantren epistemology and MI curriculum (2019–2025). Three structural gaps were identified: teacher authority is constituted administratively rather than through intellectual lineage; 78% of KD are cognitively oriented without explicit social-benefit aims; and Fikih and Akidah-Akhlak are structurally disconnected despite their epistemological interdependence in the pesantren tradition. These gaps are structural rather than incidental, with direct implications for teacher professional development, curriculum revision, and classroom practice in MI Fikih education